Street smart! : cities of the ancient world - Runestone Press. Geography Dept. (Minneapolis : The Press, 1994)
Examines, through photographs and text, ancient cities in various regions of the world including Middle East, the Americas, the Mediterranean, and Asia.
Includes index and glossary.
Child Study Children's Book Committee.
School Library Journal.
Wilson's Junior High School.
6.5
4-6
Keywords: Cities and towns, Ancient -- Juvenile literature; Cities and towns, Ancient; Cities and towns